Comparative of Conventional Marketing and Sharia Marketing Against Maslahah With Customer Satisfaction as Intervening at Customer Super Market in Batam City - Wibisono, Chabullah (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2018)
The unbalanced development of modern markets and traditional markets, of course, as a result of conventional marketing and syariah marketing systems, has the effect of many current markets and the decline of traditional markets that are mostly owned by the economically weak communities in Batam, whether the impact of conventional maketing that make the city into behaving cosumtifically, it is necessary to conduct research "Comparative of Conventional Marketing and Sharia Marketing Against Maslahah with Customer Satisfaction as Intervening at Customer Super Market In Batam City", population is taken from 8 big super market in Batam City equal to 8 x 100 respondents, sample of 215 respondents, using SEM * version 22, research result: the effect of conventional marketing variable on Customer Satisfaction variable is positively significant, variable effects Sharia Marketing to variable Customer Satisfaction is significantly positive, variable effects Customer Satisfaction to variable Maslahah is a significant negative, variable results Conventional Marketing to variable Maslahah is definite, not substantial, the effect of variable Sharia Marketing to variable Maslahah is significantly positive, changes in Customer Satisfaction influenced by Sharia Conventional Marketing and Marketing of 39.50%. Maslahah change is affected by the effects of conventional and Sharia Marketing Marketing and amounted to 53,50% customer satisfaction, consumers are dissatisfied with traditional marketing, but consumers do not get maslahah that is a dimensionless material and spiritual fulfillment, need to apply Sharia marketing.Keywords:Â Conventional Marketing, Sharia Marketing, Customer Satisfaction and Maslahah.